If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -3 = 32x Reorder the terms: -3 + 9x = 32x Solving -3 + 9x = 32x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-32x' to each side of the equation. -3 + 9x + -32x = 32x + -32x Combine like terms: 9x + -32x = -23x -3 + -23x = 32x + -32x Combine like terms: 32x + -32x = 0 -3 + -23x = 0 Add '3' to each side of the equation. -3 + 3 + -23x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -23x = 0 + 3 -23x = 0 + 3 Combine like terms: 0 + 3 = 3 -23x = 3 Divide each side by '-23'. x = -0.1304347826 Simplifying x = -0.1304347826
| 3x+2-5x=2 | | 7x^3+10=5x+20 | | (5x+1)(8x+8)= | | 12/15=/100 | | -9s/5=2 | | x+27853407564307834=73673673467324673674564 | | -0.3e+0.34=2.6e+7.85 | | -5(0.1x+0.2)-1.8=-0.3 | | 0=r^2-43.56 | | 7.50x+1=2.50 | | W^3+2w^2+19+w^2-2w-1= | | 6(7z+1)=6 | | -13=5(1+4*1)-2*1 | | y+2y-9=15 | | 8t^2-20t+5=0 | | 50+10x=30+15x | | 0=-9z^2-6z+15 | | 56x^2+23x-63= | | 8b-(-7)=9 | | 9x^2-3y=y | | -4+3.5=13.5 | | 3*tg(x)-3=0 | | 6(y-5)=5(x+5) | | 0.5(12m-22n)= | | C/1.25=22.50 | | 2y-15+3y+3=14 | | 9/n=n | | 4(n-3)=6(n+3) | | 9-n=n | | 15b^2-3a=3-7a | | n-9=n | | 3(2n+5)=-(n-50) |